Investigation of Mono-Crystalline Photovoltaic Active Cooling Thermal System for Hot Climate of Pakistan - Asim M.; Milano J.; Khan H.I.; Hanzla Tahir M.; Mujtaba M.A.; Shamsuddin A.H.; Abdullah M.; Kalam M.A. (MDPI, 2023)
climate; cooling; photovoltaic system; thermal phenomena; Lahore; Pakistan; Punjab [Pakistan]